CiptaSTEAM: An Integrative Holistic Learning Model to Enhance Students' Knowledge and Skills Competencies Simultaneously - Hendri, Zulfi; Nur Hayati; Wulandari, Dwi (Jurnal Pendidikan Anak, 2025)
Appreciation, innovation, and the competencies of knowledge and skills in learning are components that cannot be separated in both early education (Kindergarten-Elementary) and secondary education (Junior-High School). Unfortunately, educators have faced difficulties in finding a learning model that can simultaneously facilitate both knowledge and skills within a unified learning experience. The STEAM concept, which encompasses the principles of practice- and project-based learning, still requires reevaluation to be effectively integrated with the distinctive features of learning at both early and secondary education levels. This research aims to develop an integrative, holistic learning model to enhance knowledge and skill competencies based on STEAM simultaneously. This R&D study was conducted in six steps : (1) needs analysis, (2) literature review, (3) planning and development of the initial model, (4) pilot testing, (5) revision of the main model and field testing, and (6) final model revision. The study resulted in a learning model called CiptaSTEAM with the following steps: 1) Analyse, 2) Sketch/Design, 3) Select media, 4) Test sketch/design, 5) Revise work/product, 6) Presentation, 7) Evaluation. The learning syntax has been proven to be applicable in early education (Elementary). Overall, the integrative holistic learning model has been effective in increasing students' engagement and enthusiasm for learning in a 3rd-grade elementary classroom.